Effect of N, P and K on Growth and Yield of Cotton under Rainfed Condition in Red Loams of Chotanagpur - Chakravarty, R.K.; Vasudevaiah, R.D.; Teotia, S.P. Singh (Journal of Soil and Water Conservation, 2022)
Farming on the uplands of Chotanagpur consists mainly of single crop rotations with smaller millets, cereals, pulses or oil seeds and fallowing of land for a period of 2 to 3 years. Usually cultivated crops e.g. Marua, (Eleusine coracana) Gondli (panicum miliare), Desi Maize, Kulthi (Dolichos biflorus), Sarguja (Guizotia abyssinica) Urid (Phaseolus mungo) etc. do not add much to the farmers income. Naturally the return from these lands is much smaller than what it could have been, had they been cropped with remunerative crops. Development of a better source of farm income seems to be of prime importance in Chotanagpur under the existing conditions. Therefore a generally reliable cash crop is badly needed to improve low levels of living. Cotton has been found to be one of such crops which may perform the job efficiently if improved methods of cultivation are adopted. With this aim in view a full fledged experiment was taken up at Deochanda Experiment Station, DVC, to find out the effect of N,P,K, and their combinations on the growth and yield of Cotton. The experiment was taken up in 1961-62 and was run for three years that is upto 1963-64.